Anticoagulant use to treat VTE (venous thromboembolism) in pregnancy: a review - Purwandityo, Ayuningtyas Galuh; Muhammad S. Finnegan; Mukarromah D. Putri; Muya Saroh; Nindita Rachmania; Riandita G. Putri (Indonesian Journal of Pharmacology and Therapy, 2022)
Venous thromboembolism (VTE), including deep vein thrombosis (DVT) and pulmonary embolism (PE), is a medical condition that occurs when a blood clot forms in a deep vein that major cause of pregnancy-related maternal death. As pregnancy progresses, the risk of hypercoagulability increases, fibrinogen, factors VII, VIII, X and VWF (Von Willebrand Factor), plasminogen activator inhibitor-1, plasminogen activator inhibitor-2 are increases and 40-60% protein S decreases. Therefore, anticoagulant drugs are the mainstay of therapy for patients with VTE. The review aimed to select the best anticoagulant for pregnancy women with VTE. A scoping review was used. The type of articles reviewed were original articles obtained from four electronic journal databases published within 2012-2021. The main therapeutic agent recommended for use in the prevention and treatment of VTE in pregnancy is low molecular weight heparin (LMWH). LMWH has better bioavailability than other anticoagulants, has a lower risk of maternal bleeding, thromboembolic, thrombocytopenia and osteoporosis. The use of LMWH is actually better, more comfortable and safety for patients.